Educação Escolar Quilombola: currículos de formação inicial de professores em uma instituição da Rede Federal de Educação, Ciência e Tecnologia, ressignificando olhares - Libório, Andréia Regina Silva Cabral (2022)
The present doctoral research, developed in the Postgraduate Program in Education: Curriculum of the Pontifical Catholic University of São Paulo (PUC-SP), in the line of training educators, presents the following guiding question: How is Quilombola School Education constituted in the curriculum of the Degree Courses of the Federal Institute of Education, Science and Technology of São Paulo (IFSP)? The general objective is focused on: Investigating which and how the conceptions, about the knowledge in relation to Quilombola School Education, as a Teaching Modality of Basic Education and with regard to peoples and/or quilombos/quilombola communities, are evident in the Pedagogical Projects of Degree Courses of the IFSP, and, if they are developed in the curriculum throughout the academic path, in a decolonial perspective. It was anchored in the theoretical framework based on scholars of the curriculum, teacher training, diversities, cultures, interculturalism, interdisciplinarity, among others, such as: Freire (1981; 2014; 2015), Forquin (1993), Gimeno Sacristán (1999) ; 2002; 2007; 2008; 2013; 2017), Silva (1995a; 1995b; 2016), García (1992; 1999), Fazenda (2001; 2003; 2011), Morin (2003) Candau (2005; 2013; 2014), Gomes (2005a; 2005b; 2007), Arroyo (2010; 2011; 2013), Imbernón (2011), Tardif (2014), Moreira (1995), Feldmann (2003; 2008; 2009), Ponce (2018), Geertz (2008) ), Mizukami (2010), Thompson (2011), Chiavenato (2012), Masetto (2011; 2020), Giroux (2013), Pérez-Tapias (2013), Santomé (2013), Saul and Saul A. (2018), Kilomba (2019), Almeida (1998; 2004; 2008; 2011), among others, which deal with the quilombo theme, legislation and curriculum requirements on Quilombola School Education, etc. The methodology used is predominantly characterized by a qualitative approach, based on bibliographic research and document analysis techniques. The collection instruments used were a survey of the literature, official documents and open databases, and in the procedures for analyzing and interpreting data were adopted from Bardin”s “Content Analysis” (2016). The results contradict the initial assumption, pointing out that the conception about the knowledge of quilombola peoples and/or communities, as constituent subjects of Brazilian society, and Quilombola School Education (EEQ), a modality of Education, and its references are incipient, in addition to do not show the EEQ as a modality of Basic Education, as recommended by current legislation. Thus, the Courses that present some reference to the theme approach it in a superficial way, without the due depth and contextualization and, in nineteen of them, there is a total emptying and erasure of the theme in question. In addition, the importance of Quilombola School Education as a modality of Basic Education is highlighted in these teacher training curriculum, since future educators need to be prepared to work in schools located in the quilombola territories and/ or in schools that serve students from these, especially for the reception of their cultures, experiences, knowledge and daily practices related to traditional knowledge, as well as the specificities of differentiated education. Furthermore, it is necessary to reframe the view on this still unknown topic, especially in teacher training, which makes the quilombola people invisible